The Japanese Banks in the Lasting Low-, Zero- and Negative-Interest Rate Environment - Taiki Murai; Gunther Schnabl (Credit and Capital Markets – Kredit und Kapital, 2021)
The bursting of the Japanese bubble economy in the early 1990s put the stage for a lasting low-, zero-, and negative-interest rate environment, which fundamentally changed the business environment for the Japanese commercial banks. On the income side, with interest margins becoming increasingly depressed, net interest revenues declined, which forced the banks to expand revenues from fees and commissions. The banks had to cut costs by reducing the number of employees, closing branches and merging into larger banks. The gradual concentration process has most recently cumulated in the relaxation of the monopoly law. With the capital allocation function of banks being undermined, the Japanese economy has become zombified, suffering from anemic growth.
Keywords: E52; G21; E50; 330; Japan; Bank of Japan; monetary policy; banks; interest margin; financial repression; concentration; regional banks